Evaluation of Leaf Spot Resistance and Agronomic Characteristics of Groundnut Advanced Breeding Lines - Wahyu, Yudiwanti; Achmad, Achmad; Junaedi, Wahyu (Journal of Tropical Crop Science, 2016)
Leaf spot is a major groundnut disease in Indonesia and worldwidewhich has the potential to cause a yield loss of up to 60%. The use of leaf spot resistant cultivars is an easy, economical, and environmentally friendly way in groundnut cultivation to maintain high yields. The objective of the research was to evaluate the yields of 16 groundnut lines which had been developed to be leaf spot resistant and high yielding. The research was conducted in 2010 – 2011 at the Bogor Agricultural University (IPB) experimental station in Cikarawang, Indonesia. A randomized complete block design with three replications was used in the experiment. The groundnut lines evaluated were crosses between “Gajah”, a cultivar which is known to be susceptible to leaf spot, and the resistant line GPNC- WS4. Four Indonesian cultivars “Gajah”, “Jerapah”, “Zebra” and “Sima” were used as control. The results showed that selected lines demonstrated better resistance to leaf spot compared to “Gajah”. Their agronomic characteristics, such as pod number, filled pod number, pod weight, and kernel weight, were not significantly different from the control cultivars. The results of this study have provided information on groundnut leaf spot resistant lines for further evaluation.